Pelatihan Manajemen Laboratorium IPA Berbantuan Game Edukasi Kahoot bagi Laboran/Pengelola Labor - Muhammad Reza; Sitti Hasnidar; Latifah Hanum (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Science laboratories play an important role in the success of chemistry, physics, and biology education in schools. Students and teachers need facilities and infrastructure to prove the veracity of theory and to establish the relationship between theory and practice through experiential learning activities. In addition to teachers and students, the roles of research assistants and work managers are also very important to put practical learning into practice. To improve the knowledge and skills of science room management in schools, we will standardize the science room management of laboratory assistants and work instructors. This activity began with a pre-test, followed by the provision of teaching materials through lectures and discussions, quizzes through a method of promoting understanding, lab operations through a real-action approach, and a post-test. The training will be held for 4 days from August 9 to 12, 2022, at the Aceh Barat Daya District Education Office, where classroom lessons will be held, and at SMA Negri 6 Aceh, where participants will practice setting up their laboratories. It was conducted at two locations in Bharat Daya. education. Participants followed the learning process in the classroom very well as evidenced by achieving good quiz scores with an average accuracy of 7-12 out of 15 questions, or 47-80%. With Kahoot learning games, the quizzes at the end of each learning material add extra fun and motivation to learners and are very helpful in the evaluation process during the training process. Furthermore, post-test results showed that participants' knowledge increased by up to 80.4% compared to pre-test results. From this, we can conclude that this laboratory management training was properly implemented and produced very good results.